ESPAN Thematic Report on Access for children in need to the key services covered by the European Child Guarantee Cyprus - Kantaris, Marios; Andreou, Sofia N.; Chrysostomou, Stavri; Lalioti, Varvara (My University, 2023)
On 14 June 2021, the Council of the European Union adopted a Recommendation establishing a “European Child Guarantee”, with a view to guaranteeing access to six key services for “children in need”: • effective and free access to four services: high-quality early childhood education and care (ECEC); education and school-based activities; at least one healthy meal each school day; and healthcare; and • effective access to two services: healthy nutrition and adequate housing. The purpose of the present report is to assess the extent to which low-income children in Cyprus do indeed have effective (or effective and free) access to these services. There have been very decisive steps to improve ECEC in Cyprus, although it is still a weak and problematic service with significant affordability and availability issues. New policies implemented recently seem to support wider participation in ECEC by aiming to make it available and more affordable for all low-income households with children. However, there are still major challenges in implementing these measures. Even though access to education and school activities is theoretically free for all, in reality the affordability criterion does not seem to be fully met. Individual school communities (teachers and parents) are often responsible for assessing the need for exemptions, as well as for supporting and covering the costs of this service. A free meals at school programme has been in place for primary and secondary schools since 2012. Each school is responsible for assessing eligibility for this programme through a special advisory committee. However, data suggest that a significant number of children at risk of poverty and social exclusion probably do not receive a free meal every school day. The recently introduced policy for ECEC is aimed at expanding this service to children up to 4. The introduction of a new national health system that provides universal coverage regardless of income has minimised the barriers to affordable healthcare for all (including low-income children). Despite the fact that co-payments and personal contributions are required for most of these services, the very low annual caps for low-income beneficiaries have a positive impact on accessibility and affordability. The long waiting times and limited availability of some services, which affect low-income groups more, are still a major challenge, as private healthcare is not an alternative. Apart from school meals, where efforts are made to meet health criteria, the existing (limited) evidence suggests that the high cost of healthy food and inadequate social benefits are important financial barriers to the affordability and accessibility of healthy nutrition for lowincome children. There is no evidence for non-financial barriers, despite a strong indication that the concurrent presence of a chronic illness may be a non-financial barrier to this type of service. Finally, there is no housing policy that directly targets adequate housing for households with low-income children. It is obvious that the observed lack of affordable housing, overcrowding and unhealthy and deprived living conditions mainly affect low-income families. The housing schemes introduced in Cyprus in recent years, as a result of the 2012-2016 financial crisis, are based on income thresholds that are higher than the national guaranteed minimum income and the risk-of-poverty indicator values.
Access for children in need to the key services covered by the European Child Guarantee Cyprus